Guide to operating systems security - Palmer, Michael (Thomson/Course Technology, 2004)
This guide is designed to expand networking student's basic network and operating system skills to include planning, implementation and auditing of a system's security. It covers a variety of operating systems, including a Windows client operating system, Linux, Novell NetWare and Mac OS.